SEROLOGICAL TESTING FOR TUBERCULOSIS SHOULD BE BANNED - W.H.O - Hawthorne, G.; Thickett, DR; Wood, AM (Journal of Postgraduate Medical Institute, 2012)
Tuberculosis (TB) remains a major global healthcare issue with around 1.7 million deaths in 2009due to TB and rising absolute number of cases each year due to the increasing global population . Theemergence of drug resistance, worsening malnutrition in the settings of political instability and civil unrest,and the detrimental effects of HIV coinfection has challenged TB eradication programs worldwide. TheWorld Health Organisation (WHO) Stop TB strategy aims to reduce the global burden of TB by 2015. Akey component of the Stop TB strategy is to ensure early case detection and diagnosis using appropriatequality controlled bacteriology.